2017
DOI: 10.1590/0100-29452017518
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR DIAGNOSIS OF Guignardia citricarpa IN ASYMPTOMATIC SWEET ORANGE TISSUE

Abstract: RESUMO -A pinta preta ou mancha preta dos citros, causada pelo fungo Guignardia citricarpa, é considerada uma doença quarentenária, que impõe restrições ao transporte de frutas frescas para países da União Europeia. A ocorrência de infecções latentes e o tempo para o diagnóstico por métodos convencionais levam à necessidade de validar protocolos moleculares rápidos, eficientes e reprodutíveis para detecção do patógeno em tecidos assintomáticos. Assim, este trabalho visou detectar G. citricarpa em tecidos de fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This founded bacterial population is considered very critical population densities for molecular detection by PCR. For G. citricarpa conventional PCR was suitable for detecting DNA with 90% repeatability of detection at a concentration of 10 ng and 70% at a minimum of 0.01 ng according to the work of Faganello et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…This founded bacterial population is considered very critical population densities for molecular detection by PCR. For G. citricarpa conventional PCR was suitable for detecting DNA with 90% repeatability of detection at a concentration of 10 ng and 70% at a minimum of 0.01 ng according to the work of Faganello et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm those of Van Gent-Pelzer et al [21] who reported that realtime PCR with primers GcF1 and GcR1, is a rapid method for the specific detection of P. citricarpa generating much smaller amplicons of 69 bp. Faganello et al [30] reported that real-time PCR is a robust and more sensitive method than conventional PCR and allows detection of P. citricarpa in asymptomatic plant tissues. According to Schirmacher et al [31], this method can detect and distinguish P. citricarpa from other pathogens without the need for sequencing.…”
Section: Discussionmentioning
confidence: 99%